Intermittent traction therapy in the treatment of chronic low back pain - Edina Tanović; Damir Čelik; Đemil Omerović; Vanda Zovko Omeragić; Amila Jaganjac; Hadžan Konjo; Emina Rovčanin; Hana Omerović (Medicinski glasnik, 2020)
Aim: To investigate the effect of intermittent traction therapy (ITT) on pain in patients with chronic low back pain (CLBP). Methods: A total of 81 patients with CLBP were included: experimental group received ITT (n=40) and control group received conservative physical treatment (n=41) 10 times for two weeks. A visual analogue scale (VAS) was used for measuring low back pain. Results: In the experimental group, 26 (out of 40; 65.0%) patients were females, in the control group 20 (out of 41; 48.8%) were females (p=0.141). In a within-group comparison, median of VAS value was significantly decreased in both groups after ITT. A comparison of pre-intervention and post-intervention VAS value showed no statistically significant difference. Females from the experimental group had a significantly greater decrease of VAS compared with females from the control group. Patients in the ITT group with L5/S1 level of hernia had lower estimated marginal mean of VAS scale compared to the control group, as well the patients with left side of leg pain. Conclusion: Intermittent traction therapy is an effective treatment for pain reduction in patients with chronic low back pain.
Keywords: physical therapy; traction; Visual Analogue Scale